(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
The main biological and reproductive parameters of the Perela (Paralabrax spp.) are described in this paper. Perela was fished using bottom longline by the artisanal fleet from the Anconcito port in the area located from the outermost tip of the Peninsula de Santa Elena and southwards to 3º00’S– 81º00’W. Among results, the minimum and maximum sizes of the Perela were determined as 16 and 72 cm TL, respectively; and an increase in sizes from July to December in males and females was also recorded. Allometric growth for Paralabrax spp. was determined; most of organisms were mature (stages II and IV) during the study period, excepting on August, when it was found that the male and female gonads were in recovery (stage V). As a result of the gonadosomatic index test, synchronism was not observed between males and females, that could be produced by the presence of juvenile males during the month of October. The average size at maturity (L 50%) for females at 40.0 cm LT and 42.2 cm LT in males was determined by using the maximum likelihood method. Applying the average length method was determined that 68.9% of females and 83.1% of males were over the allowable average size (L 50%).